REKONSTRUKSI RATOK SILUNGKANG TUO DARI RITUAL KEMATIAN MENJADI SENI PERTUNJUKAN DALAM RANGKA PELESTARIAN BUDAYA MINANGKABAU - Arnailis Arnailis (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
T Silungkang Tuo mourn is one kind of mourn cultural that born in Silungkang Minangkabau, West Sumatera. This traditional art is used to mourn over a dead tiger. This lament / mourn didn't have an obvious text, its perfrormed by chanting without a clear articulation. The people of the Silungkang called it marunguih. Marunguih performed at night by someone inside a sheath nearby the tiger tomb. All of thing that related to the dead of the tiger is performed with marunguih, each of it had a different rhythm. This research had a purpose to learned about the value, asthetic, and also philosophy of the Silungkang Tuo Mourn background. Then it will be reconstructed to a music composition to fulfill the aesthetic standard of an art performance, without dispelling the value of its own traditional society. The methods used in this research is qualitative methods with an anthropology, aesthetic, sosiology, and musicology approach. The methods that are used to gather the data in this research is observation, interview, and documentary. The result of this research is a music composition in a theatrical form and also this research can be used to boost tourism of Silungkang.